Urgent Care for Schools : Situating Responsibility as an Engaging Way for Students to Transform School Cultures - Smith, Barbara J., (Educational Research E-Books Online, Collection 2025., 2025)
What can schools do differently to reach more students? What can educators do to address an urgent need to provide meaningful, memorable and fulfilling learning experiences? By viewing curriculum through a lens of 'situated responsibility', it is possible to engage students in authentic and purpose-based learning. This book is about expanding the student identity to include that of becoming service providers, injustice responders, action researchers, designers, apprentices and teachers. This book features a collection of international stories written by students and their advisors who care deeply about their education and supporting others. There is much we can do. Contributors are: Erin Calley, Susana Calley, Trish Cislak, Nethra Dave, Cierra Gee, Craig Griffie, James Hay, Steven Klein, Vama Kothari, Carla Johnson, Michael Johnson, Jose Antonio Gordillo Martorell, Laird McGraw, Zander Moricz, Kristy Pagnutti, Talithia Palmer, Helen Pereira-Raso, Kendahl Pollock, Vaishnave Raina, Barbara J. Smith, Kenzy Soror, Ted Spear, Stephanie Stephens, Gemma Tabet, Kyle Wagner, Emily Walton-Doris and Lauren Willms